2016
DOI: 10.1134/s0026261716020144
|View full text |Cite
|
Sign up to set email alerts
|

Screening of new isolates of Bacillus thuringiensis for cry1 genes and testing of toxicity against Dichocrocis punctiferalis (Family: Pyralidae, Order: Lepidoptera)

Abstract: In order to identify the more toxic novel cry gene, the cry1 gene was screened in six indigenous isolates of Bt by PCR with degenerate primers showed amplification in all the Bt isolates. Subsequent screening of cry1 subfamily gene(s) by gene specific primer showed amplification of cry1A gene in the five Bt isolates, three out of the six cry1 positive isolates showed the presence of cry1Aa gene. One of the six Bt isolates showed the presence of cry1Ab gene. Five Bt isolates showed amplification for cry1Ac gene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 20 publications
1
1
0
Order By: Relevance
“…PCR screening for lepidopteran toxic gene families confirmed the presence of cry1, cry1Ab, cry1Ac, cry2, cry2Aa, cry2Ab and vip3A genes in isolate T352 (Table 2). Various studies on indigenous Bt isolates revealed the cry1, cry1Aa, cry1Ab, cry1Ac, cry2Aa, cry2Ab and cry9 genes contributing the toxicity against major lepidopterous insects [24,[35][36][37][38] and the dominance of cry1 and cry2 gene existing together was usually high [39]. The Bt isolate T352 having cry1 and cry 2 along with vip3A gene and toxic to S. frugiperda was in agreement with previous studies [40].…”
Section: Pcr Screening Of Cry and Vip Genessupporting
confidence: 87%
“…PCR screening for lepidopteran toxic gene families confirmed the presence of cry1, cry1Ab, cry1Ac, cry2, cry2Aa, cry2Ab and vip3A genes in isolate T352 (Table 2). Various studies on indigenous Bt isolates revealed the cry1, cry1Aa, cry1Ab, cry1Ac, cry2Aa, cry2Ab and cry9 genes contributing the toxicity against major lepidopterous insects [24,[35][36][37][38] and the dominance of cry1 and cry2 gene existing together was usually high [39]. The Bt isolate T352 having cry1 and cry 2 along with vip3A gene and toxic to S. frugiperda was in agreement with previous studies [40].…”
Section: Pcr Screening Of Cry and Vip Genessupporting
confidence: 87%
“…Bt toxins swallowed by insect get stimulated by the midgut proteases in order to develop crystals that disrupts the midgut wall, leading to insect death. The insecticidal activity of the bacterium is dependent on the capability to develop large quantity of delta-endotoxins (Cry proteins) (Manikandan et al 2016).…”
Section: Introductionmentioning
confidence: 99%